A new species of Satyrichthys (Teleostei: Peristediidae) from the Maldives Archipelago (Indian Ocean) - Pogoreutz, Claudia; Vitecek, Simon; Ahnelt, Harald (Zootaxa, 2013)
A new species of the genus Satyrichthys, Satyrichthys kikingeri sp. nov., is described from the Rasdhoo Atoll, Maldives Archipelago. The new species is placed in a group of Satyrichthys with at least three lip barbels and unequal parietal bones. It differs from its congeners in the combination of the following characters: (1) 3/3 lip and 1/0 chin barbels, (2) 15 fin rays in the second dorsal fin, 13 fin rays in the anal fin, (3) 25 bony plates in the dorsal, 29 in the upper lateral and 20 in the lower lateral rows, (4) 21st to 28th bony plates in the upper lateral row with forward directed spines and (5) parietal bones unequal in size on midline. Satyrichthys kikingeri sp. nov. is the first Satyrichthys species reported from the Republic of the Maldives.